Modelos Y Estilos De Resolución De Conflictos En El Marco De Una Cultura De La Paz Para Los Líderes De Las Unidades Habitacionales Del Municipio De Puebla, México - Cervantes, Leticia Susana Medoza; Mendoza, Susana Pérez Milicua (European Scientific Journal, ESJ, 2018)
This paper focuses on the different theories on management and styles of conflict resolution in order to establish a culture of peace among the leaders of the housing units of the municipality of Puebla, Mexico. The literature was reviewed using keywords in different databases. The main findings suggest that there is a great diversity of models and styles of conflict resolution, as well as different instruments to evaluate them. However, its focus is fundamentally oriented to organizational reality, rather than to issues of a social nature. The model and style of conflict resolution that best explains the prevailing situation in housing units is the two-dimensional approach with four styles.